LEVELS OF NICOTINE ADDICTION IN CONSUMERS OF THE LATEST TOBACCO PRODUCTS - Svitlana Kozii-Bredelieva; Iryna Kovalska (Acta Medica Leopoliensia)
Aim. Determining the level of nicotine addiction in consumers of the latest tobacco products.